THE EFFECT OF TEACHING PHONOLOGICAL RULES ON ENGLISH PRONUNCIATION AMONG IRANIAN PRE-INTERMEDIATE EFL LEARNERS - Ehsan Namaziandost; Fariba Rahimi Esfahani (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2019)
This study was intended to examine the impact of teaching phonological rules on English pronunciation among Iranian pre-intermediate EFL learners. To fulfill, 50 pre-intermediate students who were studying in a private language institute in Ahvaz, Iran were selected via non-random sampling (convenience sampling). They participated in a homogeneity test (Oxford Quick Placement Test) to determine their homogeneity level. Then they were randomly divided into two groups of control (n=25) and experimental (n=25). Before starting the treatment, a validated teacher-made pronunciation test was administered to both groups as the pre-test. Then the experimental group received the treatment, which was teaching phonological rules activities and the control group received conventional instruction including examples in an implicit method. At the end of the treatment, a post-test on pronunciation was administered to evaluate the effect of phonological rules instructions to assess the participants’ pronunciation improvement. At the end of the study, the analysis of the obtained data was carried out using SPSS, version 25. The obtained results indicated that there was a significant difference between the performances of both groups. The experimental group participants were found to have a better performance than the control group. Generally, the experimental group outperformed the control group. This study suggests that teaching phonological rules can help learners to learn pronunciation more easily and effectively. Keywords: Assimilation Rules, Phonological Rules, English Pronunciation